Maladaptive Daydreaming: Epidemiological Data on a Newly Identified Syndrome - Soffer-Dudek, Nirit; Theodor-Katz, Nitzan (Frontiers in Psychiatry, 2022)
Background: Maladaptive Daydreaming (MD) is a recently-identified psychological disorder, characterized by excessively and addictively engaging in vivid, narrative, intensely emotional fantasy activity, at times with the aid of music and/or repetitive movements, causing distress and functional impairment. Over 100,000 self-diagnosed individuals are active online and thousands of them have been researched; yet there are no studies using clinical interviews on large, systematic general (non-MD) samples, to assess the estimated prevalence of this suggested disorder, and establish norms for its main psychometric tool. Methods: Four independent Israeli samples (three student samples, and one sample representing the general Jewish-Israeli population; total N=1,023) self-reported MD. In two samples, those exceeding the cutoff score for suspected MD were invited for a structured clinical interview. Results: The skewness of most items of the Maladaptive Daydreaming Scale (MDS-16) supports the notion of MD as a binary construct rather than a normally distributed trait. In the community sample, 4.2% exceeded the cutoff for suspected MD. Rates were higher when focusing on the young adult age group or student samples (5.5%-8.5%). Following clinical interviews, only 60% of interviewed respondents met criteria for diagnosis, suggesting a true point-prevalence of 2.5% in the Israeli-Jewish population. Conclusions: In a systematic clinical evaluation of the prevalence of MD in Israel, we found a point-prevalence of 2.5%, like several other internalizing psychiatric syndromes, and a non-normal nature of item distribution. This supports the validity of MD as a psychological disorder that should be considered as a potential addition to future psychiatric diagnostic manuals.